2016
DOI: 10.1037/fsh0000227
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a measure of primary care behavioral health integration.

Abstract: These data suggest that the PIP is useful, has face, content, and internal validity, and distinguishes among types of practices with known variations in integration. We discuss how the PIP may support practices and policymakers in their integration efforts and researchers assessing the degree to which integration affects patient health outcomes. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 17 publications
1
41
0
2
Order By: Relevance
“…The new six‐item Integration and Sharing Methods domain retains a high degree of internal consistency, even after including the two items formally in the Workspace Arrangements and Infrastructure domain. This change also makes intuitive sense as the Integration and Sharing Methods domain, “covers the type and degree of interactions among medical and behavioral providers.” The inclusion of questions assessing physical proximity and shared documentation in this domain is consistent with the domain's focus.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The new six‐item Integration and Sharing Methods domain retains a high degree of internal consistency, even after including the two items formally in the Workspace Arrangements and Infrastructure domain. This change also makes intuitive sense as the Integration and Sharing Methods domain, “covers the type and degree of interactions among medical and behavioral providers.” The inclusion of questions assessing physical proximity and shared documentation in this domain is consistent with the domain's focus.…”
Section: Discussionmentioning
confidence: 72%
“…A validated measure of behavioral health integration will help identify integration activities that are associated with improved patient outcomes. Previous studies have demonstrated the reliability and validity of the PIP . Since the initial validation studies were conducted, 1000 additional PIPs have been completed, resulting in a more robust database.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations